Treating chronic atrophic gastritis: identifying sub-population based on real-world TCM electronic medical records - Wang, Yu-man; Sun, Jian-hui; Sun, Run-xue; Liu, Xiao-yu; Li, Jing-fan; Li, Run-ze; Du, Yan-ru; Zhou, Xue-zhong (Frontiers in Pharmacology, 2024)
Objective Based on the complex network and clinical research integration platform to analyze CAG case patterns and provide ideas and methods for accurate medical and clinically personalized treatment, Methods We analyzed data based on CAG medical records to construct a similar network of patients with shared symptoms and conducted association testing for population segmentation. We explored the clinical characteristics and symptom-drug relationships of different subgroups based on efficacy. Symptom-drug molecular features were identified by GO and KEGG enrichment analyses. Results 5132 patients were included. The population was divided into 176 modules. We selected the first 3 modules to illustrate the characteristic phenotypes and genotypes of CAG disease subtypes. The top symptoms for symptom improvement in all three subgroups were stomach pain, bloating, insomnia, poor appetite, and heartburn. However, the three groups were different. The M29 subgroup was more likely to have stomach distention, anorexia, and palpitations. Citrus medica, Solanum nigrum, Jiangcan, Shan ci mushrooms, and Dillon were the most popular drugs. The M3 subgroup has a higher incidence of yellow urine, a bitter tongue, and stomachaches. Smilax glabra, Cyperus rotundus, Angelica sinensis, Conioselinum anthriscoides, and Paeonia lactiflora were the drugs used. Vomiting, nausea, stomach pain, and appetite loss are common in the M0 subgroup. The primary medications are Scutellaria baicalensis, Smilax glabra, Picrorhiza kurroa, Lilium lancifolium, and Artemisia scoparia. In the M29 subgroup, Citrus medica, Solanum nigrum, Jiangcan, mushrooms, and Dillon may exert their therapeutic effects on the symptoms of gastric distension, anorexia, and palpitations by modulating apoptosis and NF-κB signaling pathways. In the M3 subgroup, Smilax glabra, Cyperus rotundus, Angelica sinensis, Conioselinum anthriscoides, and Paeonia lactiflora may be treated by NF-κB and JAK-STAT pathway for the treatment of stomach pain, bitter mouth, and yellow urine. In the M0 subgroup, Scutellaria baicalensis, Smilax glabra, Picrorhiza kurroa, Lilium lancifolium, and Artemisia scoparia may exert their therapeutic effects on poor appetite, stomach pain, vomiting, and nausea through the PI3K-Akt pathway. Conclusion: The classification of the CAG population based on PSN and community detection can provide important guidance for clinical treatment. It is practical to study CAG disease classification and genotype.